Enhancing Rubisco gene expression and metabolites accumulation for better plant growth in Ficus deltoidea under drought stress using hydrogen peroxide - Khandaker, Mohammad Moneruzzaman; Jamaludin, Rosnah; Majrashi, Ali; Rashid, Zalilawati Mat; Karim, Sarker Mohammad Rezaul; Al-Yasi, Hatim M.; Badaluddin, Noor Afiza; Alenazi, Mekhled Mutiran; Mohd, Khamsah Suryati (Frontiers in Plant Science, 2022)
Growth improvement of the medicinal plant, Ficus deltoidea under drought conditions is a vital issue in Malaysia since it is slow-growing plant and disposed to leaf damage under the stresses of drought. Therefore, investigation was done to examine the outcomes of hydrogen peroxide (H₂O₂) application on RuBisCo gene expression of stressed F. deltoidei plants, and thereby to record the changes in leaf histology, photosynthesis, biochemical properties, and the growth of the plant. H₂O₂ at the rates of 0, 5, 15 and 20 mM were foliar sprayed biweekly to the drought stressed plants using a hand sprayer. The application of 20 mM H2O2 amplified leaf number, tallness, stomatal conductance, and photosynthetic yield by 143%, 24%, 88% and 18%, respectively, over the control plant. A reduced transpiration rate and improved chlorophyll fluorescence were also noted in H2O2-treated plants. The treatment produced greater amount of chlorophyll a, total phenols, total flavonoids, sugar content and antioxidant activities by 1.61-, 1.30-, 1.98-, 1.92- and 1.53-fold, respectively. Application of 15 mM H2O2 enhanced net photosynthetic rate and internal CO2 concentrations by 1.05- and 1.25-fold, respectively. Additionally, H₂O₂ treatments promoted stomatal closure, increased stomata size, the number of stomata, improved vein structure and reduced the damage of the leaf margin and mesophyll cells of drought stressed plants. The application of H2O2 also produced significantly higher contents of sodium (Na+), calcium (Ca2+), potassium (K+), magnesium (Mg+) and iron (Fe2+) in stressed plants. Although the amount of Arsenic (As+) and Antimony (Sb3+) increased to some extent, but the increases were not at toxic level. The using of H2O2 enhanced the Rubisco gene expression to a greater level and the ratio of Rubisco expression increased up to 16-fold. The GCMS analysis showed that the foliar application of H2O2 accumulates higher percentage of volatile components in plants which helps to mitigate the negative effects of drought stress. It is concluded that under drought stressed conditions the F. deltoidea plants should be treated with 10-15 mM of H₂O₂ twice a week to improve leaf histology, photosynthesis, the level of Rubisco gene and volatile compounds, plant growth and development.